Caracterização de feições cársticas desenvolvidas em quartzitos na região sudeste de Diamantina/MG - Fernanda Cristina Rodrigues de Souza (2014)
The main objective of this study is to characterize the karst features developed in Espinhaço Supergroup quartzite rocks, in the southeastern region of Diamantina, associating them with lithostructural and geomorphological factors inherent in the development of these forms. For this, the methodological procedure included: a) literature review and mapping in b) exokarstic and fluviokarstic karst features investigation; c) kamenitzas geostatistical characterization d) caves characterization in its geographical context of insertion; e) caves morphological characterization; f) macroscopic characterization of laminated clastic deposits; g) chemical analysis and microscopic characterization of chemical deposits; h) characterization of lithostructural and geomorphological contexts of the insertion of the caves; i) interpretation of the local geographical context, its relationship to the karst features development and its correlation with the data obtained. The results demonstrate that the study area records the existence of exokarstic and fluviokarstic features, as well as presents higher occurrence potential than mapped. The interpretation of kamenitzas descriptive statistics reveals that there are two kamenitzas morphological types in the study area: a) the deep, rounded and smaller ones and b) the shallow, elongated or oval and larger ones. During the prospecting activities, ten caves and 32 shelters were identified, all features were mapped and georeferenced. After the prospection, 70% of the caves sample number, which is a number of seven caves, was selected for detailed interpretation. The selection criteria included: occurrence of hydrologic processes, horizontal projection upper 5m and the chemical deposits presence. In accordance to the criteria used for characterization and description of caves, the occurrence of hydrological processes in all the caves stands out. These processes occur in the forms of dripping, condensation and perennials and intermittent drainages. The clastic deposits occur in the form of sand, silt, pebbles and boulders distributed along the ducts. Some laminated clastic deposits are also noted in four caves (Salitre, Monte Cristo, Extração and Curralinho Caves). The main organic deposits observed in the caves are leaves, roots and guano. Finally, the chemical deposits are found in all the caves and occur especially in the form of coralloides, scabs, silica dams and bleeding. All the seven caves in the studied area are predominantly flatter. The conduits morphology of the studied caves presents the ceiling and floor morphologies gently sloping and is predominantly concordant to the trim direction of the slope. Generally, the galleries and halls have rectangular, triangular and elliptical horizontal morphologies. The qualitative studies using SEM and EDS line in samples of chemical deposits in the study area indicate varieties of chemical elements, especially Ca, Si and Na. The chemical deposits microscopic images using the SEM data indicate variations in the mineral concentration and indicate probable fluctuations in environmental conditions favorable to the development of speleothems. The relationship between lithostructure, geomorphology, climate and hydrography may have contributed to the formation of caves and exokarstic features in the the SE region of Diamantina. The polymineralogical and polytextural rock composition favors the development of karst features. Structural factors associated to the caves development in the SE region of Diamantina are primarily the fracture planes, followed by dipping bedding and foliation planes. Therefore, the interaction between these types of structural lineaments contributes to the formation and planform of existing caves. The local geomorphology contributes to the development of caves, since the occurrence of caves agrees to the slope inclination and there is a positive relationship between the gradient of the slope and the local relief of the caves. Also noteworthy is that the presence of escarpments dissected is a favorable area to the occurrence of caves, which happens because it contributes to the mechanical remobilization of altered grains. Accordingly, it appears that the geographical context consisting of several conditions favors the karst features presence in the SE region of Diamantina/MG.